Metro Manila's 2019 water crisis: Of efficiency traps and dry taps. Issue 2 (17th September 2021) - Torio, Philamer C.; Mendoza, Ronald U.; Torres, Ayn G.
Abstract: In 2019, Metro Manila experienced a water supply crisis, barely 2 years after the government and its private concessionaires were given international recognition for a successful water privatization, with success defined in terms of high operating efficiencies and improved service levels. These service‐level improvements, however, brought about a surge in consumer demand, which necessitated the construction of a new water supply infrastructure. Regulatory failures resulting in nondelivery of the infrastructure effectively negated and trapped the efficiency gains that were built slowly over the years, at a cost of US5.4 billion. Such failures resulted in public indignation over dry household taps, as well as a presidential anger that threatened to cancel the program in its entirety. Using the lessons learned from this crisis, the paper enumerates measures to help unlock the traps set by these regulatory failures. Abstract: 2019年, 马尼拉大都会经历了一场水供应危机, 而在两年前, 政府及其私人特许经销商因成功的水私有化而受到国际认可, 这种成功被界定为高运作效率和服务程度提升。不过, 服务程度的提升引起消费者需求的激增, 后者让新的水供应基础设施成为必需。一系列监管失败导致无法交付基础设施, 有效阻止并套牢了过去几年里逐步取得的效率利益, 成本为54亿美元。这类失败之举导致公众对干涸的家用水龙头感到愤怒, 总统也气愤扬言将取消这一整个计划。通过应用从此次危机中汲取的经验, 本文列举了一系列措施, 以期帮助解除由监管失败导致的效率陷阱。 Abstract: En 2019, Metro Manila experimentó una crisis de suministro de agua, apenas dos años después de que el gobierno y sus concesionarios privados obtuvieran el reconocimiento internacional por una privatización exitosa del agua, con el éxito definido en términos de altas eficiencias operativas y niveles de servicio mejorados. Sin embargo, estas mejoras en el nivel de servicio provocaron un aumento en la demanda de los consumidores que requirió la construcción de una nueva infraestructura de suministro de agua. Las fallas regulatorias que resultaron en la falta de entrega de la infraestructura efectivamente negaron y atraparon las ganancias de eficiencia que se construyeron lentamente a lo largo de los años, a un costo de US 5, 4 mil millones. Tales fallas dieron como resultado la indignación pública por los grifos domésticos secos, así como una ira presidencial que amenazó con cancelar el programa en su totalidad. Utilizando las lecciones aprendidas de esta crisis, el documento enumera las medidas para ayudar a desbloquear las trampas establecidas por estas fallas regulatorias.